OPPORTUNITIES AND PROBLEMS OF USING DIGITAL TECHNOLOGIES IN TEACHING HISTORY (Universal International Scientific Journal, 2026)
This scientific article provides a comprehensive analysis of the theoretical and practical aspects of using digital technologies in the process of teaching history. The aim is to identify the impact of digital tools on educational effectiveness, their didactic capabilities, and existing problems. Digital technologies play an important role in deepening historical knowledge, developing students' critical thinking, and organizing interactive learning. At the same time, there are problems such as the lack of technical infrastructure, low levels of digital literacy, and the reliability of information. At the end of the study, practical recommendations are given to eliminate these problems.
Keywords: digital technologies, history education, interactive methods, pedagogical innovations, digital literacy, distance learning, virtual learning